How to Create a Friendly Environment for Innovation? A Case for Europe - Ege, Aylin; Ege, A. Yavuz (Social indicators research, 2019)
It is a misjudgement to assume that R & D subsidies, patent protections or alike are sufficient to promote innovation. In fact, innovations incubate and hatch within an environment, especially if it is a friendly one. The aim of this paper is to look for the major factors which are the building blocks or pillars of such an environment. After discussing and analysing the theoretical and empirical studies on the major social and political factors which are the likely constituents of our inquired environment, four major blocks or pillars appear to be the basic components on theoretical grounds. They are identified as the four different categories of inclusiveness, namely legal/regulatory, political and economic, social, and informatory. A model is developed by employing variables representing these four groups to measure and to analyse their impact on innovation. The model is tested by utilising the panel data of European countries. The results indicate that a favourable environment for innovation requires the existence of rule of law, gender equality, economic and political stability, and access to information.